2014
DOI: 10.48550/arxiv.1410.0459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulated identification of epidemic threshold on finite-size networks

Panpan Shu,
Wei Wang,
Ming Tang
et al.

Abstract: Epidemic threshold is one of the most important features of the epidemic dynamics. Through a lot of numerical simulations in classic Susceptible-Infected-Recovered (SIR) and Susceptible-Infected-Susceptible (SIS) models on various types of networks, we study the simulated identification of epidemic thresholds on finite-size networks. We confirm that the susceptibility measure goes awry for the SIR model due to the bimodal distribution of outbreak sizes near the critical point, while the simulated thresholds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Differing from the SIS (Susceptible-Infected-Susceptible) model, it is not an easy thing to determine the epidemic threshold for the SIR model owing to the non-zero value of R. In doing so, in Ref. 28 , Shu et al suggested that the variability measure…”
Section: A Results On Er Networkmentioning
confidence: 99%
“…Differing from the SIS (Susceptible-Infected-Susceptible) model, it is not an easy thing to determine the epidemic threshold for the SIR model owing to the non-zero value of R. In doing so, in Ref. 28 , Shu et al suggested that the variability measure…”
Section: A Results On Er Networkmentioning
confidence: 99%
“…2(c) later. Note that given the contacting randomness in the CP model [33,34], there is a large fluctuation of Δr R , especially near the critical point [35].…”
mentioning
confidence: 99%